Rapid bilateral visual loss as the initial clinical manifestation in idiopathic hypertrophic cranial pachymeningitis. Issue 5 (6th May 2022) - Shao, Weiyang; Tian, Chunyu; Gao, Lixiong; Cui, Bei; Shi, Qian
Abstract: A 59‐year‐old patient presented with 4‐day acute painless bilateral visual loss, MRI results showed dura enhancement of the frontal, anterior cranial fossa. The patient was considered to have idiopathic hypertrophic cranial pachymeningitis based on laboratory tests and MRI data. After treatment with hormones, the visual acuity obviously improved. Abstract : We reported a patient presented with 4‐day acute painless bilateral visual loss, who was diagnosed to have idiopathic hypertrophic cranial pachymeningitis based on laboratory tests and MRI data, the visual acuity obviously improved after timely treatment. Therefore, Intracranial changes should be considered in patients with a sharp decline in visual acuity but with no obviously positive signs of the eye fundus.